A general framework for dynamic epistemic logic: towards canonical correspondences. Issue 1 (3rd April 2017) - Motoura, Shota
Abstract : We propose a general framework for dynamic epistemic logics (DELs). It consists of a generic language for DELs and a class of structures, called model transition systems (MTSs), that describe model transformations in a static way. An MTS can be viewed as a two-layered Kripke model and consequently inherits standard concepts such as bisimulation and bounded morphism from the ordinary Kripke models. In the second half of this article we add the global operator to the language, which enables us to define the notions of a canonical MTS and canonicity of a DEL formula for a property of MTSs. Using these notions, we clarify correspondences between axioms of DELs and properties of MTSs.